The Relationship Between Understanding of Financial Management and Problem-Solving Ability With The Performance of Junior High School Principals in Bekasi District - Nufus, Izkia; Muthi, Ibnu; Haryono, Pauzan (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study aims to determine the relationship between understanding financing management (X1) and problem-solving abilities (X2) with the performance of school principals (Y) in the Bekasi district, both partially and together. This research uses quantitative research methods. Data collection techniques with questionnaires. Data analysis used Partial T Test and F Test. The results showed that there was a relationship between variable X1 and variable Y where the tcount > ttable (7,402 > 1.652) and the relationship between X2 and Y variables with tcount > ttable (6,404 > 1.652). Whereas for the F Test where X1 and X2 are against Y, Fcount > Ftable which means X1 and X2 jointly affect Y. From the results of the study, it can be concluded that there is a relationship between management understanding and problem-solving abilities with the performance of school principals both partially and collectively -The same.